2014
DOI: 10.1007/s10714-014-1827-7
|View full text |Cite
|
Sign up to set email alerts
|

Conformally flat polytropes for anisotropic matter

Abstract: We analyze in detail conformally flat spherically symmetric fluid distributions, satisfying a polytropic equation of state. Among the two possible families of relativistic polytropes, only one contains models which satisfy all the required physical conditions. The ensuing configurations are necessarily anisotropic and show interesting physical properties. Prospective applications of the presented models to the study of super-Chandrasekhar white dwarfs, are discussed.Comment: 9 pages Revtex-4, 6 figures. To app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 49 publications
(66 reference statements)
5
105
0
Order By: Relevance
“…Such duplets have been determined in [2] (see figures (3,4) for the case I, and (8,9) for the case II, in that reference). Also, the absolute numerical values of the perturbations of the parameters were taken of the order of 10 −6 , the results are not qualitatively sensitive, to changes in some orders of magnitude, below or above, that figure.…”
Section: Resultsmentioning
confidence: 92%
“…Such duplets have been determined in [2] (see figures (3,4) for the case I, and (8,9) for the case II, in that reference). Also, the absolute numerical values of the perturbations of the parameters were taken of the order of 10 −6 , the results are not qualitatively sensitive, to changes in some orders of magnitude, below or above, that figure.…”
Section: Resultsmentioning
confidence: 92%
“…Obviously α satisfies Eqs. (43) and (51), while the radial speed of sound satisfies the sufficient condition Eq. (36).…”
Section: Tangential Pressure and The Main Pair Of Inequalitiesmentioning
confidence: 99%
“…Several models were given with p r = 0 or prescribed λ. Recently, a conformally flat model with polytropic equation of state was discussed [43]. More solutions have been given by other authors [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…First, we evaluate 0 , and η for both cases by integrating Eqs. (13), (15), (16), and (17) with boundary conditions [13] …”
Section: Perturbations In Casementioning
confidence: 99%
“…Herrera and Barreto [12] discussed a general formalism for relativistic isotropic as well as anisotropic polytropes of a spherically symmetric matter distribution and constructed the Lane-Emden equation, which represents the inner structure of compact objects. Herrera et al [13] examined the stability of spherically symmetric anisotropic conformally flat polytropes using the Tolman mass and found that the considered polytropic models are stable. The perturbation technique plays a crucial role in the stability of astrophysical objects.…”
Section: Introductionmentioning
confidence: 99%